EXAMINING LIFE EXPECTANCY PATTERNS BY REGION, COUNTRY, AND GENDER IN AFRICA - Alfred Ayo Ayenigba; Abraham Soji Taiwo (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tadulako, 2026)
This study examines life expectancy patterns across 54 African countries, utilizing secondary data from the World Health Organization (WHO) and Statista. Employing descriptive statistics, a paired sample t-test, and a Wilcoxon signed-rank test, the analysis reveals pronounced regional disparities: North Africa records the highest average life expectancy (73.2 years), followed by Southern Africa (65.9 years), East Africa (64.1 years), West Africa (63.3 years), and Central Africa (61.9 years). A statistically significant female longevity advantage of 4.40 years (t = 19.18, p < 0.001; Wilcoxon Z = 6.1, p < 0.001) is observed consistently across all regions, with the widest gender gap in Southern Africa (6.2 years) and the narrowest in East Africa. Eritrea is a notable anomaly, where male life expectancy marginally exceeds female by 0.3 years. These findings underscore the need for gender-sensitive health policies and targeted regional interventions to address persistent health inequities across Africa.